Finansowa zdolność regionu - charakterystyka i sposoby realizacji - Karlin, Mykoła I. (Przegląd Prawno-Ekonomiczny, 2012)
Streszczenie dostępne wyłącznie w języku angielskim: In the article the essence of economic category “financial possibility of region” is found out, exposed ways of its providing, found out problems of interbudgetary relations in Ukraine and offered ways of their decision.